Beyond Survival: How Smart Digital Marketing is Powering the Post-Pandemic Boom (International Journal of Environmental Sciences, 2025)
This study looks at how digital marketing tactics are changing to better connect customers in the time after the pandemic. Businesses have relied more and more on digital marketing tools to keep in touch with customers, raise brand recognition, and boost sales during and after the Covid-19 pandemic, when platforms quickly moved online. The goal of this research study is to examine how well social media marketing, SEO, and personalized content marketing work at getting people to interact with brands more. Fifty people from different businesses were asked to fill out an online poll and use a quantitative research method for the study. The study used descriptive statistics, association analysis, and Bayesian regression models in SPSS to look at the data. The slope numbers for social media marketing and SEO are 0.62 and 0.58, respectively, which means they are the best ways to guess how involved customers will be. Personalized content marketing still works, but it only makes people slightly more likely to take part. The results show how important it is to have a digital marketing plan with SEO, social media marketing, and personalized content to get the most out of your audience. Businesses have problems like not having enough resources and not being able to figure out the return on investment (ROI) of their digital marketing efforts. The study also talks about these problems. But the study also finds a lot of opportunities for businesses, especially since digital tools let them reach more people and make things more personalized. This research contributes to the existing research on digital marketing that has been done since the pandemic. It shows that digital marketing techniques are very useful for getting people involved. It is helpful for companies that want to make their marketing better and change with the times in the digital world.